Cranial and peripheral neuropathy due to Epstein-Barr virus infection. Issue 861 (July 1997) - Gavin, C.; Langan, Y.; Hutchinson, M.
Abstract : A case of Epstein-Barr virus infection with neurological complications is described. An 18-year-old man developed cranial neuropathy and peripheral sensorimotor polyneuropathy three weeks after a sore throat. Though severely affected initially, he made a good recovery and no specific therapeutic intervention appears to have influenced his clinical course.